2020
DOI: 10.1007/s00228-019-02813-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral iron and calcium supplement on the pharmacokinetics and pharmacodynamics of molidustat: an oral HIF–PH inhibitor for the treatment of renal anaemia

Abstract: Purpose The present studies assessed the drug-drug interaction of molidustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor, with iron and calcium supplements, which are common medications in patients with anaemia due to chronic kidney disease (CKD). Methods Forty-two healthy men received molidustat alone (fasted or fed) or combined with oral iron(II) or calcium(II), given immediately before or between 4 h before and 1 h after molidustat in three randomized, open-label, crossover studies (12-15 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Comparable effects were observed for C max of molidustat (twofold increase), although only a mild reduction in systemic exposure to the glucuronide M1 was found (−15%). The effects of UGT inhibition on EPO turnover were much less pronounced than on the PK of molidustat, confirming the exposure‐response relationship observed in other studies 2,48 . Molidustat administered concomitantly with atazanavir was well tolerated.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Comparable effects were observed for C max of molidustat (twofold increase), although only a mild reduction in systemic exposure to the glucuronide M1 was found (−15%). The effects of UGT inhibition on EPO turnover were much less pronounced than on the PK of molidustat, confirming the exposure‐response relationship observed in other studies 2,48 . Molidustat administered concomitantly with atazanavir was well tolerated.…”
Section: Discussionsupporting
confidence: 85%
“…The effects of UGT inhibition on EPO turnover were much less pronounced than on the PK of molidustat, confirming the exposure-response relationship observed in other studies. 2,48 Molidustat administered concomitantly with atazanavir was well tolerated. Given that molidustat dosing will follow a haemoglobin-guided individual dose titration, molidustat may be administered together with atazanavir.…”
Section: Discussionmentioning
confidence: 96%
“…Physicians should understand the pharmacologic profiles (Table 1) of each HIF-PHI based on clinical trial data, [8][9][10][11][12][13][14] initiate HIF-PHI at an appropriate dose, and adjust HIF-PHI to achieve the Hb target stipulated in the guidelines of each country.…”
Section: Summary At a Glancementioning
confidence: 99%
“…Moreover, hypoxia-inducible factor-prolyl hydroxylase (HIF-PF) inhibitors have emerged as beneficial therapeutic agents for the treatment of renal anemia. Lentini S. et al showed the potential benefit of combined intake of iron supplements and HIF-PF inhibitors in patients with renal anemia [38] . Therefore, iron therapy along with other agents like HIF-PF inhibitors in iron-deficient HF patients with concomitant renal anemia or CKD may prove to be helpful.…”
Section: Discussionmentioning
confidence: 99%